Combustion of round hydrogen microjet in a concurrent flow. (November 2019) - Kozlov, V V; Grek, G R; Litvinenko, M V; Litvinenko, Yu A; Tambovtsev, A S; Shmakov, A G
Abstract: Experimental data on the diffusion combustion of round hydrogen microjet in concurrent coaxial flows are presented. The effects on combustion of the concurrent flow of air and that of air premixed with nanopowder of TiO2 are of interest. The hydrogen microjet is emanated from a round micronozzle which is surrounded by a coaxial slit to produce the concurrent flow. Combustion events found in the present conditions are similar to those observed in the previous studies on diffusion combustion of hydrogen microjets at subsonic and supersonic velocities. In a subsonic range, the so-called "bottleneck-flame region" is generated close to the nozzle exit, while in high-speed conditions the flame separates from the nozzle. At increasing velocity of both the hydrogen microjet and the concurrent flow, the "bottleneck-flame region" is still found and the combustion becomes more intense. The "bottleneck-flame region" is suppressed at the microjet velocity approaching transonic values.